Virtual school for preschooler using virtual reality technology - Yap, May Kee (2014)
Preschool is the first exposure for the children with education and preparation for the primary school. Many parents and teachers faced the problem where children refuse being left alone at preschool as the children having difficulties in adapting to the new environment. In order to solve this problem a Virtual Preschool using Virtual Reality Technology was developed to help the preschooler getting familiar with the school environment, gain virtual experience and excitement to go to school. This application was developed using unity3D and Autodesk Maya in windows platform which consists of 4 learning activities. The four activities are storytelling, drawing, learn ABCs' and mini games. In the testing phase, questionnaires, interview and observation approach has been used to identify the users' acceptance among teachers, parents and children. Results from the survey shows the users agreed that the application is interesting, attractive and capable to help the children to gain excitement to go to school.